Sciatic nerve injury following analgesic drug injection in rats: A histopathological examination - Habib Bostan; Murat Çabalar; Serdar Altınay; Yıldıray Kalkan; Levent Tumkaya; Ayhan Kanat; Sabri Balık; Adem Erkut; Dudu Altuner; Ziya Salihoğlu; Abdulkadir Koçer (İstanbul Kuzey Klinikleri, 2018)
INTRODUCTION[|]Sciatic nerve neuropathy can be observed following intramuscular gluteal injections. The histopathological examination of sciatic nerve damage following intramuscular injection in the gluteal region for acute pain treatment is not feasible in humans due to the inability to dissect and examine the nerve tissue. To overcome this issue, we used a rat model for demonstrating damage to the sciatic nerve tissue after the application of commonly used drug injections.[¤]METHODS[|]We investigated possible damage following the intramuscular injection of diclofenac, lornoxicam, morphine, and pethidine in a rat model based on histopathological characteristics such as myelin degeneration, axon degeneration, epineurium degeneration, fibrosis, epineurium thickening, perineurium thickening, lymphocyte infiltration, vacuolization, and edema.[¤]RESULTS[|]All the analgesic drugs used in our study induced histopathological changes in the sciatic nerve. Anti-S100 positivity, showing nerve damage, was found to be the lowest in the group treated with diclofenac. Neurotoxic effects of diclofenac on the sciatic nerve were greater than those of the other drugs used in the study. Lornoxicam induced the least histopathological changes in the nerve.[¤]DISCUSSION AND CONCLUSION[|]Diclofenac induced severe nerve damage not only after direct injection in the sciatic nerve but also after injection in the area around the nerve. Thus, we recommend restricting the use of intramuscular gluteal injections of diclofenac. Intramuscular use of morphine and pethidine should also be overviewed.[¤]